Parental education, Family Health Climate and accelerometer-based measured physical activity and sedentary behavior of primary school-aged children - Ziegeldorf, Alexandra; Hottenrott, Nina; Moritz, Johanna; Wagner, Petra; Wulff, Hagen (Frontiers in Public Health, 2024)
Sociodemographic factors such as parental education level (ED) influence physical activity (PA) and sedentary behavior (SED) of primary school aged children. In this context, family factors, such as the physical activity related family health climate (FHCPA), are relevant. However, the effect of FHCPA on the interaction between ED and children's activity behavior has not been investigated yet. Therefore, this study aimed to analyze the mediating effect of the FHCPA on the relation between parental ED and children's device-based measured PA and SED. A total of 94 children and their parents participated in the study. Questionnaires were used to assess parental ED and FHCPA. Children's moderate-to-vigorous physical activity (MVPA) and SED were measured using accelerometers. Bivariate correlations were conducted to investigate associations between parental ED and MVPA/SED/FHCPA. Mediation analyses were used to investigate the role of FHCPA in the association between maternal and paternal ED and children's MVPA/SED. Results indicate a small correlation between maternal ED and FHCPA for the total sample (ρ=.318, p<.001) and a medium correlation for girls only (ρ=.570, p<.001). Mediation analyses showed no significant mediation effect. However, there was a significant direct association considering FHCPA in the relation between higher maternal ED and SED in girls compared to lower ED. Future research should examine more complex models to further develop and sharpen to facilitate the derivation of more effective recommendations for health prevention programs, particularly for mothers and girls.